Analysis of Electronic Medical Record Implementation at Tirta Harja Community Health Center, Banyuasin Regency in 2026 - Rinaningsih Rinaningsih; Nani Sari Murni; Lilis Suryani (LPPM Institut Pendidikan Nusantara Global, 2026)
The implementation of the Electronic Medical Record (EMR) is part of the digital transformation of health services mandated by the Ministry of Health of the Republic of Indonesia for all health service facilities, including Community Health Centers (Puskesmas), as regulated under Ministerial Regulation of Health of the Republic of Indonesia Number 24 of 2022. However, EMR implementation in remote and riverine areas still faces various challenges, whether from the aspect of human resources, technological infrastructure, or organizational support. The Tirta Harja Community Health Center Technical Implementation Unit (UPTD Puskesmas), Banyuasin Regency, began implementing EMR in 2024, yet its execution has not been optimal across all service units. This study aims to analyze EMR implementation at UPTD Puskesmas Tirta Harja in 2026, covering the implementation process, obstacles encountered, human resource understanding and readiness, and the supporting factors for successful implementation. The study used a qualitative design with a descriptive-analytical approach. Data were collected through in-depth interviews, observation, and document review of 14 informants selected purposively, consisting of the Head of the Puskesmas, the EMR coordinator, doctors, midwives, nurses, registration staff, and P-Care officers. Data were analyzed using the Miles and Huberman interactive model with source and method triangulation. The results show that EMR implementation has proceeded gradually and is supported by the commitment of leadership and health workers, but is still at the adaptation stage. Policy communication has been carried out through socialization and training, but the dissemination of information related to application updates has not been fully even. Human resources demonstrated good commitment despite varying digital competence, while technological facilities—particularly the number of devices and the stability of the internet network—remained the main obstacles. The disposition of health workers toward EMR was generally positive, with initial resistance that was temporary in nature. The main supporting factors included leadership commitment, the existence of Standard Operating Procedures (SOPs), health worker motivation, and a culture of mutual assistance among staff. This study recommends continuous strengthening of human resource capacity, improvement of internal communication mechanisms, periodic updating of SOPs, and the provision of adequate information technology infrastructure in order to optimize EMR implementation at Puskesmas in riverine areas.